Incidence of Hypoglycemia After Gastric Bypass vs Sleeve Gastrectomy: A Randomized Trial - Capristo, Esmeralda; Panunzi, Simona; De Gaetano, Andrea; Spuntarelli, Valerio; Bellantone, Rocco; Giustacchini, Piero; Birkenfeld, Andreas L; Amiel, Stephanie; Bornstein, Stefan R; Raffaelli, Marco; Mingrone, Geltrude (The journal of clinical endocrinology and metabolism, 2018)
Abstract Context We compared the incidence of hypoglycemia after Roux-en-Y gastric bypass (RYGB) vs sleeve gastrectomy (SG). Design, Setting, and Main Outcome Measures Randomized, open-label trial conducted at the outpatient obesity clinic in a university hospital in Rome, Italy. The primary aim was the incidence of reactive hypoglycemia (<3.1 mmol/L after 75-g oral glucose load) at 1 year after surgery. Secondary aims were hypoglycemia under everyday life conditions, insulin sensitivity, insulin secretion, and lipid profile. Results Of 175 eligible patients, 120 were randomized 1:1 to RYGB or SG; 117 (93%) completed the 12-month follow-up. Reactive hypoglycemia was detected in 14% and 29% of SG and RYGB patients (P = 0.079), respectively, with the effect of treatment in multivariate analysis significant at P = 0.018. Daily hypoglycemic episodes during continuous glucose monitoring did not differ between groups (P = 0.75). Four of 59 RYGB subjects (6.8%) had 1 to 3 hospitalizations for symptomatic hypoglycemia vs 0 in SG. The static β-cell glucose sensitivity index increased after both treatments (P < 0.001), but the dynamic β-cell glucose sensitivity index increased significantly in SG (P = 0.008) and decreased in RYGB (P = 0.004 for time × treatment interaction). Whole-body insulin sensitivity increased about 10-fold in both groups. Conclusions We show that reactive hypoglycemia is no less common after SG and is not a safer option than RYGB, but RYGB is associated with more severe hypoglycemic episodes. This is likely due to the lack of improvement of β-cell sensitivity to changes in circulating glucose after RYGB, which determines an inappropriately high insulin secretion. We found that reactive hypoglycemia is no less common after SG than after RYGB, but RYGB is associated with more severe hypoglycemic episodes.